The prostaglandin F synthase activity of the human aldose reductase AKR1B1 brings new lenses to look at pathologic conditions. - Bresson, Eva; Lacroix-Péppin, Nicolas; Boucher-Kovalik, Sofia; Chapdelaine, Pierre; Fortier, Michel A. (Frontiers in Pharmacology, 2012)
Prostaglandins are important regulators of female reproductive functions to which aldose reductases exhibiting hydroxysteroid dehydrogenase activity also contribute. Our work on the regulation of reproductive function by prostaglandins (PGs), lead us to the discovery that AKR1B5 and later AKR1B1 were highly efficient and physiologically relevant PGF synthases. PGE2 and PGF2α are the main prostanoids produced in the human endometrium and proper balance in their relative production is important for normal menstruation and optimal fertility. Recent evidence suggests that PGE2 and PGF2α may constitute a functional dyad with physiological relevance at least as important as the prostacyclin-thromboxane dyad in the vascular system. We have recently reported that AKR1B1 was expressed and modulated in association with PGF2α production in response to IL-1β in the human endometrium. In the present study, we show that the human AKR1B1 (gene ID: 231) also known as ALDR1 or ALR2 is a functional PGF2α synthase in different models of living cells and tissues. Using human endometrial cells, prostate and vascular smooth muscle cells, cardiomyocytes and endothelial cells we demonstrate that IL-1β is able to up regulate COX-2 and AKR1B1 proteins as well as PGF2α production under normal glucose concentrations. We show that the promoter activity of AKR1B1 gene is increased by IL-1β particularly around the multiple stress response region (MSRR) containing two putative antioxidant response elements (ARE) adjacent to TonE and AP1.We also show that AKR1B1 is able to regulate PGE2 production through PGF2α acting on its FP receptor and that aldose reductase inhibitors (ARIs) like alrestatin, statil (ponalrestat) and EBPC exhibit distinct and characteristic inhibition of PGF2α production in different cell models. The PGF synthase activity of AKR1B1 represents a new and important target to regulate ischemic and inflammatory responses associated with several human pathologies.